THE ROLE OF TRANSFORMATIONAL LEADERSHIP OF MADRASAH PRINCIPALS IN STRENGTHENING TEACHERS’ PEDAGOGICAL COMPETENCE: A LITERATURE REVIEW - Abid Sholihin (UIN Sunan Gunung Djati Bandung, 2026)
Teachers’ pedagogical competence serves as a fundamental pillar in enhancing educational quality, especially in madrasah institutions that integrate academic instruction with Islamic values. Amid contemporary educational dynamics, the transformational leadership of madrasah principals is regarded as a strategic approach to advancing teacher professionalism, particularly in planning, implementing, and evaluating instruction. This study aims to systematically examine the relationship between transformational leadership and the reinforcement of teachers’ pedagogical competence through a narrative literature review approach. Data were collected from 18 relevant national and international journal articles published within the last five years, then analyzed using thematic content synthesis. The findings indicate that key dimensions of transformational leadership idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration play a significant role in fostering pedagogical innovation, critical reflection, and professional collaboration among madrasah teachers. Moreover, the integration of Islamic values into leadership practices enhances the contextual effectiveness of this model. This article contributes conceptually by broadening the understanding of value-based educational leadership and serves as a reference for the development of leadership training programs for madrasah principals and policies aimed at improving teacher quality. The study also recommends future empirical investigations using quantitative or mixed-methods approaches to validate the findings in broader educational settings.